KESANTUNAN BERBAHASA RETORIC INTERPERSONAL MASYARAKAT SUNDA SEBAGAI ALTERNATIF PENGEMBANGAN BAHAN AJAR MATA KULIAH SOSIOLINGUISTIK - Kartini, Ari (Universitas Nusantara PGRI Kediri, 2016)
ABSTRACTIn general the studies to be conducted aims to develop learning the local culture, the culture of Sunda to be applied through character education in improving student politeness STKIP Garut. The plan of activities to be implemented in this study were 1); describe the situation on the ground regarding the rhetorical politeness interperonal Sundanese society; 2) conduct theoretical studies about the characteristics of interpersonal speaking of polite rhetoric in Sundanese cultural perspective; 3) applying the results of theoretical studies through the development of teaching materials Sosiolinguistik. This research is a qualitative research so that the method used is descriptive-analytic method. Where this penelian only describe and develop teaching materials and courses Sociolinguistics Pragmatics in STKIP Garut. The results of observations about the behavior of the public modesty hometown village Kudang Wanajaya Wanaraja Garut districts, showed that people's behavior Sunda